The geek way : the radical mindset that drives extraordinary results - McAfee, Andrew (Little, Brown and Company, 2023)
"We're living in a time of amazing technological innovation, but we're not paying enough attention to one of the most important innovations of all--one that's going to be a wellspring of progress for a long time to come. This innovation lies with the company itself--the collection of people and assets brought together to create goods and services and bring them to market. And, as Andrew McAfee persuasively argues, this new model is pioneered by geeks who are instituting a radical new mindset, shifting the paradigm of what a business can--and should--be"--